PENGARUH PENERAPAN AKUNTANSI SEKTOR PUBLIK DAN PENGAWASAN INTERNAL TERHADAP KINERJA INSTANSI PEMERINTAH DAERAH DENGAN GOOD GOVERNANCE SEBAGAI VARIABEL INTERVENING PADA BPKAD KOTA SURAKARTA - Naufi Rosty Tsabita; Aris Eddy Sarwono; Bambang Widarno (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to examine the influence of Public Sector Accounting Implementation and Internal Control on the Performance of Local Government Agencies with Good Governance as an intervening variable at BPKAD Surakarta City using a quantitative approach. The sample in this study consisted of 50 respondents, who were employees of BPKAD Surakarta City. The sampling technique used purposive sampling. The results of the study indicate that Public Sector Accounting Implementation has a significant negative effect on Good Governance, while Internal Control has a significant positive effect on Good Governance. Public Sector Accounting Implementation shows a negative and insignificant effect on the performance of local government agencies, whereas Internal Control and Good Governance both have a significant positive effect on performance. However, Good Governance is unable to mediate the relationship between Public Sector Accounting Implementation and Internal Control on the performance of local government agencies.